Determinants of Parental Willingness to Provide HPV Vaccination for Adolescents in Indonesia: A Systematic Literature Review - Silvia Hanjani; Akmal Firmanda Surya; Fita Amanda Putri; Pramudya Dhiwang Nugroho; Shichachul Izzah; Siwi Pramatama Mars Wijayanti; Sri Nurlaela; Novita Endang Fitriyani (Jurnal Ilmu Kesehatan Masyarakat, 2026)
HPV vaccination is a highly effective strategy for reducing the burden of cervical cancer in Indonesia. However, its uptake among adolescents remains limited due to low parental awareness and socioeconomic disparities. This review aims to identify key determinants influencing parental acceptance or hesitancy toward HPV vaccination, providing evidence to optimize national vaccination strategies for adolescents. This PRISMA-guided systematic review included original open-access studies published between 2015 and 2025, examining determinants of parental acceptance regarding HPV vaccination among Indonesian adolescents aged 9-15 years. Predefined Boolean terms were used to identify relevant articles retrieved from Google Scholar, PubMed, ScienceDirect, and Garuda, yielding 14 studies that met the eligibility criteria and were included in the final analysis. Parental willingness and acceptance of HPV vaccination in Indonesia are influenced by individual knowledge and attitudes, social and normative pressures, economic constraints, health literacy, and the role of healthcare providers. Higher levels of knowledge, positive attitudes, supportive social norms, and access to trusted health information promote acceptance, whereas safety concerns, perceptions of the child’s age, and low-income act as significant barriers. Strengthening free school-based programs and integrating vaccination within the existing reproductive health services emerges as a solution to increase parental acceptance towards HPV vaccination among their adolescents.